Direct Leaching of Vanadium from Vanadium-bearing Steel Slag Using NaOH Solutions: A Case Study. (19th May 2021) - Wan, Junfeng; Du, Hao; Gao, Feng; Wang, Shaona; Gao, Minglei; Liu, Biao; Zhang, Yi
ABSTRACT: Vanadium-bearing steel slag is a typical solid waste in the steel industry and a valuable secondary resource for vanadium production. In this paper, a direct alkaline leaching process was proposed to extract valuable vanadium and achieve comprehensive utilization of the residue by incorporating the new process into the conventional Bayer alumina production process. The leaching mechanism showed the feasibility of alkaline leaching. The effects of alkaline concentration, temperature, particle size, liquid-solid ratio (mass ratio), and stirring speed on the process were investigated, and the recovery of vanadium was found to achieve 68.4% under optimal conditions. Both the internal diffusion and the interface reaction were found by kinetic analysis to be the controlling steps of the leaching reaction, and the apparent reaction activation energy value of 26.67 kJ/mol was calculated. The valence state of the vanadium in the steel slag was analyzed in detail, finding that low-valent (V 3+ ) and high-valent (V 4+ and V 5+ ) vanadium were both present in the steel slag. By introducing oxygen into the reaction system, the recovery could be improved to 85.6%, which was 17.2% higher than that of non-oxidative leaching.